2016
DOI: 10.1099/jgv.0.000628
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mutations in live infectious bronchitis vaccine viruses following single or dual in vitro infection of tracheal organ cultures

Abstract: Despite regular co-vaccination of two different strains of live infectious bronchitis vaccine viruses, little is known about possible mutations in these viruses following vaccination. As an alternative to chicks, this study used an in vitro infection model to identify single-nucleotide polymorphisms (SNPs) within the part-S1 gene of two live infectious bronchitis virus vaccine strains (793B and Massachusetts) following single or dual inoculation onto tracheal organ cultures. Results indicate that viral titres … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…With both experiments, Sanger sequencing showed that the genotype of strains recovered using OP swabs altered from Mass to 793B after 14 dpv. As reported previously [26,27], while the Mass genotype made up the majority of detections during early sampling days (3-14 dpv), the 793B strain became the dominant strain by 21 dpv. The reason for the shifting of genotypes from Mass to 793B is not known, however, previous work has highlighted that different IBV strains can differentially induce host expression pathways, in particular TLR7 [65] and IFN-b [66].…”
Section: Ibv Ampvsupporting
confidence: 83%
See 1 more Smart Citation
“…With both experiments, Sanger sequencing showed that the genotype of strains recovered using OP swabs altered from Mass to 793B after 14 dpv. As reported previously [26,27], while the Mass genotype made up the majority of detections during early sampling days (3-14 dpv), the 793B strain became the dominant strain by 21 dpv. The reason for the shifting of genotypes from Mass to 793B is not known, however, previous work has highlighted that different IBV strains can differentially induce host expression pathways, in particular TLR7 [65] and IFN-b [66].…”
Section: Ibv Ampvsupporting
confidence: 83%
“…Recent work has shown that IBV vaccines can undergo genetic mutations following inoculation into the chicken host [26,27]. As persistent mutations can alter strain characteristics [28], it is preferable to monitor potential changes.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, IBV vaccination programs have gained more attention with respect to the use of low-virulent, live or inactivated killed vaccines with the aim of booster shots at certain times to increase immunity and reduce the antagonistic response of epithelial cells in the respiratory region [89]. However, there is a significant limitation in applying live IBV vaccines because the attenuation of the vaccine is naturally deficient with respect to its capability in stimulating a mucosal immune response [90,91], which is a critical part of controlling IBV infection since killed vaccine can be an option [92,93]. Nonetheless, it was possible that inactivated killed vaccines can be applied to stimulate t mucosal immune responses once combined with several nanoparticles [92].…”
Section: Vaccine Development Against Ibvmentioning
confidence: 99%
“…In addition, attenuated IBV strains used for vaccination can spread among individual birds within flocks [ 121 ], and changes in virulence during bird-to-bird passage can lead to production problems [ 120 , 122 ]. Coinfection of host cells with live attenuated IB vaccines and wild type IBV can also result in genomic recombination contributing to the virus evolution [ 11 , 123 ] as well as mutations that can occur under the effect of immune pressure [ 124 , 125 , 126 ]. Although the global poultry industry practices hatchery vaccination against IB, Day 1 may not be the optimum time for vaccination in terms of inducing systemic and mucosal immune responses against IB [ 106 ] because of the developing immune system [ 127 ].…”
Section: Vaccine Mediated Ib Controlmentioning
confidence: 99%
“…Given the available scientific evidence against IB vaccination at the hatchery [ 106 , 110 ], it may also be appropriate to postpone the first IB vaccination to a barn vaccination done at seven days of age relying on maternal antibody response to protect the chickens during the first week of life [ 110 ]. There are numerous issues surrounding the use of live attenuated IB vaccines [ 11 , 99 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 ], and relying on inactivated vaccines can be an option, but they inherently lack the ability to induce mucosal immune response, which is critical for the control of IB [ 131 , 132 , 133 ]. It is possible that inactivated vaccines can be used for the induction of mucosal immune response when combined with various nanoparticles [ 132 ].…”
Section: Vaccine Mediated Ib Controlmentioning
confidence: 99%